2009
DOI: 10.3109/08039480903274423
|View full text |Cite
|
Sign up to set email alerts
|

Using brief self-reports and clinician scales to screen for substance use disorders in psychotic patients

Abstract: We conclude that the SMAST-13 and DAST-20 in combination with the AUS and DUS, which are easy and quick to perform, are helpful in establishing a common understanding of the patient's alcohol and drug problems in an early intervention clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…For example, researchers have found that adults with schizophrenia under-reported their drug use during an acute crisis, but not when their symptoms were stabilized (Stone et al 1993). Similar research has found that one out of seven adults who entered an early intervention program for psychosis under-reported their use of drugs on measures that relied on self-rated use (Møller & Linaker, 2010). Studies of in-patients and out-patients with schizophrenia have documented considerable underreporting of cocaine use, which was revealed when reports that relied on what patients self-rated about their drug use were compared with positive urine tests (Shaner et al 1993), and similar research showed that none of the patients with positive urine tests disclosed their use of drugs (Galletly et al 1993).…”
Section: Introductionmentioning
confidence: 91%
“…For example, researchers have found that adults with schizophrenia under-reported their drug use during an acute crisis, but not when their symptoms were stabilized (Stone et al 1993). Similar research has found that one out of seven adults who entered an early intervention program for psychosis under-reported their use of drugs on measures that relied on self-rated use (Møller & Linaker, 2010). Studies of in-patients and out-patients with schizophrenia have documented considerable underreporting of cocaine use, which was revealed when reports that relied on what patients self-rated about their drug use were compared with positive urine tests (Shaner et al 1993), and similar research showed that none of the patients with positive urine tests disclosed their use of drugs (Galletly et al 1993).…”
Section: Introductionmentioning
confidence: 91%
“…The measure has been widely used in a number of psychosis spectrum studies (Cannon et al, 2008; Mittal et al, 2011; Mittal et al, 2012; Dean et al, 2014; Carol, E., and Mittal, V.M., under review) and shows excellent reliability (Long and Hollin, 2009; Moller and Linaker, 2010). …”
Section: Methodsmentioning
confidence: 99%
“…No data cutoff scores. 12,15,25,32,43 Further, a study of mothers of children in a pediatric practice demonstrated that the DAST-20 failed to identify mothers who used drugs inappropriately within the past 24 hours. 30 One publication on the DAST-A, a version developed for use in adolescent psychiatric inpatients, demonstrated high internal consistency and 1-week test-retest reliability; adolescents with drug dependency diagnoses scored higher on the DAST-A than did other groups, demonstrating its validity, and showed that a cutoff score greater than 6 was associated with moderate sensitivity and good specificity in predicting DSM-III-Revised (DSM-III-R) and DSM-IV drug-related disorders.…”
Section: Patient-reported Instruments: Nonspecificmentioning
confidence: 96%
“…A cutoff score of 5 was associated with 74% sensitivity and 66% specificity using the staff-reported Clinical Drug Use Scale as the criterion (phi coefficient = .34 15 3. Relationship between 20-item DAST and problematic drug use, drug use disorder diagnoses, and clinician-rated problematic drug use 12,15,25,30,43,53 ; distinction between 20-item DAST items and alcohol abuse items 50 4. No data 5.…”
Section: Patient-reported Instruments: Nonspecificmentioning
confidence: 99%
See 1 more Smart Citation